MEMAKSIMALKAN KONTRIBUSI AMIL UNTUK PEMBERDAYAAN UMAT - Lubis, Muhammad Arifin; Amalia, Rahmi (HUMAN FALAH: Jurnal Ekonomi dan Bisnis Islam, 2024)
Empowering the community is one of the main goals in the Islamic economic system, and zakat collectors (amil zakat) play a crucial role in realizing this objective. This study aims to explore how the contribution of amil zakat can be maximized for community empowerment through more effective and optimal zakat management. In this context, amil zakat not only functions as a collector and distributor of zakat but also as an agent of change who can direct zakat towards sustainable empowerment programs. This study uses a qualitative approach with descriptive analysis to explore the factors that influence the effectiveness of amil zakat in community empowerment, including training, zakat management based on accurate data, and enhancing the capacity of amil zakat in designing empowerment programs that meet the needs of the community. The findings indicate that enhancing the capacity of amil zakat, in terms of knowledge, skills, and understanding of community empowerment principles, can significantly impact the sustainability of social and economic programs for recipients of zakat (mustahik). Therefore, maximizing the contribution of amil zakat is a strategic step in realizing the social-economic goals of Islam in empowering the community.